1999
DOI: 10.1007/s002469900468
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular Involvement in a Boy with Sweet's Syndrome

Abstract: Acute febrile neutrophilic dermatosis (Sweet's syndrome) is a rare disease in infancy. It may present in an isolated manner or be associated with diverse conditions. Only two children with postinflammatory slack skin who developed cardiovascular disease have been described to date, both of whom died from coronary artery occlusion. We report a boy with Sweet's syndrome and diffuse vascular disease involving the aorta and the supraaortic vessels, the pulmonary trunk, and the right coronary artery but without sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
38
0
3

Year Published

2007
2007
2019
2019

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(41 citation statements)
references
References 11 publications
0
38
0
3
Order By: Relevance
“…Other first-line systemic treatments for Sweet's syndrome are potassium iodide and colchicine (Table 10) [10,12,17,20,23,30,49,70,143,184,198,203,221,223,231,240,245,250,259,261,281,284,294,296,329,359-363,368-384,397,410]. …”
Section: Managementmentioning
confidence: 99%
See 2 more Smart Citations
“…Other first-line systemic treatments for Sweet's syndrome are potassium iodide and colchicine (Table 10) [10,12,17,20,23,30,49,70,143,184,198,203,221,223,231,240,245,250,259,261,281,284,294,296,329,359-363,368-384,397,410]. …”
Section: Managementmentioning
confidence: 99%
“…Second-line agents for treating Sweet's syndrome include indomethacin, clofazimine, cyclosporin, and dapsone (Table 11) [1,12,17,20,30,203,221,231,245,259,261,284,294,296,372,378-384,421]. All of these agents have been used as monotherapy either in the initial management of the patient or after first-line therapies have failed.…”
Section: Managementmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the long interval of up to 7 years between Sweet's syndrome and cardiological diagnosis, some authors suggest an acquired (auto-) inflammatory process leading to a parallel inflammation of cutis and vessels with cutis laxa representing the postinflammatory state of the skin [48,21]. Alternatively, and in view of the phenotypic overlap between Loeys-Dietz syndrome, a recently described autosomal dominant aortic-aneurysm syndrome with widespread systemic involvement due to mutations in the genes encoding transforming growth factor beta receptors 1 and 2 [42] and vascular Ehlers-Danlos syndrome, a genetic defect could also come to mind.…”
Section: Discussionmentioning
confidence: 99%
“…Hwang's case had coexisting α 1 ‐antitrypsin deficiency, suggesting that the lack of natural protease inhibitors may allow inflammatory processes to produce the elastic tissue destruction 10 . Review of the literature (Table 1) revealed that there were at least three other cases of acquired cutis laxa following Sweet's syndrome 11–13 . As shown in the table, all of these patients were below the age of 2 years and had extensive skin lesions.…”
Section: Discussionmentioning
confidence: 99%